First Conjugate Observations of Medium‐Scale Traveling Ionospheric Disturbances (MSTIDs) in the Europe‐Africa Longitude Sector. Issue 3 (25th March 2019) - Martinis, Carlos; Baumgardner, Jeffrey; Mendillo, Michael; Wroten, Joei; MacDonald, Timothy; Kosch, Michael; Lazzarin, Monica; Umbriaco, Gabriele
Abstract: All‐sky imagers located in Asiago, Italy (45.87 o N, 11.53 o E; 40.7 o magnetic latitude) and Sutherland, South Africa (32.37 o S, 20.81 o E; −40.7 o magnetic latitude) are used to study magnetically conjugate medium scale traveling ionospheric disturbances (MSTIDs). We present initial results from the first year of joint Asiago‐Sutherland data sets from July 2016 to June 2017. The 630.0‐nm airglow perturbations showing different kinds of waves were frequently observed. Some of these wave events resemble MSTIDs propagating south‐westward in Asiago, typical direction observed at other longitude sectors in the northern hemisphere. They are mostly observed as single bands propagating through the field of view of the all‐sky imagers. We select and analyze five cases of magnetically conjugate bands associated with MSTIDs. The bands observed at Sutherland move mainly westward, noticeably different from the north‐west direction of propagation of MSTIDs observed in the southern hemisphere. We compare the MSTIDs propagation speeds and find that three cases show larger values at Sutherland. When we compare the zonal speeds all the cases show larger values at Sutherland. On average, the propagation speed at Sutherland is 20% larger and the zonal speed is ~35% larger. The westward motion at Sutherland is explained by taking onto account how its magnetic declination (~24 o W) affects the orientation of the bands. The larger speed at Sutherland is due to the weaker Earth's magnetic field in the southern hemisphere and the particular configuration of the magnetic field lines in this longitude sector. Key Points: MSTIDs observed at conjugate locations in the Europe‐Africa longitude sector for the first time Direction of propagation of Sutherland MSTIDs is mostly westward, consequence of its large magnetic declination Propagation speeds are larger at Sutherland due to weaker Earth's magnetic field and its configuration at this longitude sector